Some luck [compact disc, unabridged] - Smiley, Jane (Smiley, Jane. Last hundred years., 2014)
On their farm in Denby, Iowa, Rosanna and Walter Langdon abide by time-honored values that they pass on to their five wildly different yet equally remarkable children: Frank, the brilliant, stubborn first-born; Joe, whose love of animals makes him the natural heir to his family's land; Lillian, an angelic child who enters a fairy-tale marriage with a man only she will fully know; Henry, the bookworm who's not afraid to be different; and Claire, who earns the highest place in her father's heart.